Implementation of Malay leadership Tunjuk Ajar Melayu in Political Communication for Malay Women Leaders - Shasrini, Tessa; Saputra, Hamanda Hadi; Sukri, Al (Institut Komunikasi dan Bisnis LSPR, 2025)
The values of Tunjuk Ajar Melayu are a cultural heritage that reflects local wisdom in various aspects of life, including in political communication. This study aims to analyze how the values of Tunjuk Ajar Melayu are implemented in the political communication of Malay women's leadership. The research method used is a qualitative approach with in-depth interview techniques and discourse analysis of speeches and political interactions of Malay women leaders. The results of the study show that Malay women leaders apply the values of Tunjuk Ajar Melayu in their political communication through three main aspects: (1) polite and persuasive language, which is used to build emotional relationships with the community; (2) the principle of deliberation and consensus, which is the basis for decision-making and building understanding in the community; and (3) exemplary moral and ethical leadership, which is reflected in an attitude of humility, honesty, and responsibility in carrying out leadership duties. The implementation of these values not only strengthens the legitimacy of Malay women's leadership but also builds public trust, strengthens relationships with the community, and creates harmonious and effective political communication. In conclusion, the implementation of Tunjuk Ajar Melayu in the political communication of Malay female leaders plays an important role in forming an inclusive, ethical, and social harmony-oriented leadership style. This study shows that local cultural values remain relevant in modern political dynamics and can be a sustainable model of political communication.